2000
DOI: 10.4049/jimmunol.165.2.888
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Human B Cell Lymphoma Xenografts with a CD3 × CD19 Diabody and T Cells

Abstract: The use of anti-CD3 × antitumor bispecific Abs is an attractive and highly specific approach in cancer therapy. Recombinant Ab technology now provides powerful tools to enhance the potency of such immunotherapeutic constructs. We designed a heterodimeric diabody specific for human CD19 on B cells and CD3ε chain of the TCR complex. After production in Escherichia coli and purification, we analyzed its affinity, stability, and pharmacokinetics, and tested its capacity to stimulate T cell proliferation and mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 50 publications
3
47
1
1
Order By: Relevance
“…Another important question is if BIS20x3 is more efficient in treating lymphomas than CD19xCD3 bispecific antibodies. Several CD19xCD3 bispecific antibodies have been described recently (Daniel et al, 1998;Cochlovius et al, 2000;Löffler et al, 2000) in several antibody-formats (quadroma-derived, bi-specific singlechain and diabody respectively). The findings that CD20 seems to be higher expressed on B-cells compared to CD19 and that CD20 is not internalized after antibody binding in contrast to CD19-antibody complexes are often used as arguments for the use of CD20 antibodies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another important question is if BIS20x3 is more efficient in treating lymphomas than CD19xCD3 bispecific antibodies. Several CD19xCD3 bispecific antibodies have been described recently (Daniel et al, 1998;Cochlovius et al, 2000;Löffler et al, 2000) in several antibody-formats (quadroma-derived, bi-specific singlechain and diabody respectively). The findings that CD20 seems to be higher expressed on B-cells compared to CD19 and that CD20 is not internalized after antibody binding in contrast to CD19-antibody complexes are often used as arguments for the use of CD20 antibodies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,18,21 Monospecific anti-CD3 tanDb was assembled from OKT3-derived V H and V L domains 23 essentially as described for CD19ϫCD3 tanDb. 15 Gene constructions were performed according to standard DNA manipulation techniques, and the experimental details are available from the authors upon request.…”
Section: Recombinant Moleculesmentioning
confidence: 99%
“…19 We previously demonstrated that CD19ϫCD3 BsDb is more effective than quadroma-derived bispecific antibody at mediating T-cell cytotoxicity in vitro against tumor cells. 13,18 Although BsDb was relatively rapidly cleared from the blood through the kidneys, its antitumor activity in animal tumor models was closely similar to that of the much larger quadroma-derived bispecific antibody. 18,20 However, the BsDb is formed by heterodimerization of 2 different gene products, which must be expressed in the same cell in similar amounts.…”
mentioning
confidence: 96%
See 2 more Smart Citations